Hubungan Tingkat Kecemasan dan Dukungan Sosial terhadap Kepatuhan Pasien Menjalankan Terapi Hemodialisis di Rumah Sakit Umum Pusat H. Adam Malik Medan - Suriati Suriati; Mappeaty Nyorong; Nuraini Nuraini (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
Compliance running hemodialysis therapy is needed by patients with Chronic Renal Failure. Hemodialysis therapy aims to remove excess urea and other nitrogenous wastes that circulate in the blood. This study is observational analytic cross-sectional design which aims to analyze the influence of anxiety and social support on patient adherence running hemodialysis therapy. The population in this study were all patients undergoing hemodialysis therapy at the Adam Malik General Hospital in 2020 the number of 86 people. This study was conducted from January to June 2020. Data was obtained through interviews with respondents and analyzed by multiple logistic regression at 95% confidence level. The results showed that the variables of anxiety (p = 0.030) and social support consisting of support information (p = 0.003), support assessment (p = 0.033), instrumental support (p = 0.027) and emotional support (p = 0.010) associated with adherence running hemodialysis. It is recommended to the hospital management inorder to provide information (counseling) to patients undergoing hemodialysis therapy for the patient to understand the actions undertaken so as not to cause anxiety in the patient and the family.